Highly efficient organic electroluminescent device with modified cathode - Choulis, Stelios A.; Mathai, Mathew K.; Choong, Vi-En (My University, 2006)
One of the key parameters for high efficiency organic electrophosphorescent light emitting diodes is charge injection into the phosphorescence compound. By introducing a hybrid device architecture, and incorporating electron and hole interfacial layers with lowest unoccupied molecular orbital and highest occupied molecular orbital levels similar to that of the phosphorescence compound, on the cathode and the anode side of the device, respectively, charge injection properties were improved. A green electrophosphorescence device with luminous efficacy of 50 lm/W at luminance efficiency reaching 55 cd/A was demonstrated
Keywords: Cathodes; Electrons; Light emitting diodes; Phosphorescence